Smart Environment Monitoring System by Using Sensors Ultrasonic Detection of Farm Pests - AHOUANDJINOU, SÈMÈVO ARNAUD ROLAND MARTIAL; ASSOGBA, KOKOU MARC; KIKI, Probus M. A. F. (My University, 2017)
We live in the age when all things are becoming smarter, wireless and more connected. A lot of products and devices which we use in our daily lives are already smart. Furthermore, our living spaces are becoming smarter like Smart houses, and pervasive environments are nowadays no longer science fiction but rather more and more realistic. In this work, we propose a smart sensor in wireless network architecture which is able to detect the ultrasound of farm pests. This smart sensor is based on an ultrasonic transducer and four stages amplifier circuit built around the op-amp LM324. This assembly allow to have a signal shape very close to the signal supplied by the transducer. This sensor will help many in the early detection of insects pests and to anticipate their attacks by setting up a protocol to exterminate them. The main contribution of this work is to limit the risk of environmental diseases resulting from agricultural practices for healthy health. To this end, we have designed an intelligent sensor that detects the presence of pests through an acquisition of ultrasound that they emit so quick and avoid competent advisory of countermeasures to farmers. By way of experimentation, an electrical signal from the transducer has been simulated to test the sensor and it amplifier system performance.
Keywords: smart System; Wirless sensors network; Environment Monitoring; Agroecology